A nucleoside diphosphokinase from liver mitochondria which catalyzes an [ 32P] ADP-ATP exchange reaction - Chiga, M.; Plaut, G.W.E. (Biochimica et biophysica acta, 1962)
A nucleoside diphosphokinase has been purified 50- to 100-fold from aqueous extracts of porcine-liver mitochondria. The enzyme can catalyze transphosphorylation reactions between a number of nucleoside di- and triphosphates, e.g., an exchange between [ 32P] ADP and ATP, and accounts for a substantial portin of the ADP-ATP exchange activity of such extracts. The ADP-ATP exchange is not catalyzed. The reaction is activated by Mg 2+ or Mn 2, and is not inhibited by low concentrations of sulfhydryl-group binding agents.